Perbedaan Akhlak di Tinjau dari Kecerdasan Emosional dan Kecerdasan Spiritual Siswa - Wahid, Abdul; Wahyuningsih, Retno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine; Moral differences between high and low emotional intelligence; Moral differences between high and low spiritual intelligence; and Moral differences in terms of the interaction between emotional intelligence and spiritual intelligence in students at State Junior High Schools in Sidoharjo District for the 2020/2021 academic year. The research method used is comparative quantitative using t-test analysis and two-way ANOVA in public junior high schools throughout the Sidoharjo district from October to December 2020. The population in this study was the entire class of class VIII SMP Negeri in Sidoharjo district, as many as 507 students. The sample is some students, as many as 221 students. The results showed: 1) there were moral differences between students who had high and low emotional intelligence, because a significance value of 0.000 <0.05 was obtained. 2) there is a difference in morals between students who have high and low spiritual intelligence because a significance value of 0.000 <0.05 is obtained. 3) there are differences in morals in terms of the interaction of emotional intelligence and spiritual intelligence, the results of the hypothesis show sig. 0.001 < 0.05. In conclusion, there is an interaction between high emotional intelligence and low spiritual intelligence, high spiritual intelligence and low emotional intelligence on morals. Key words: Akhlak, emotional intelligence, spiritual intelligence